Silent enemy of the hand: The Viking disease - Stoiljković Vera (Halo 194)
Dupuytren's contracture (DK) is the most common progressive idiopathic fibrosis of the superficial palmar fascia, often asymptomatic at its onset, caused by changes in the palmar aponeurosis, resulting in flexion contractures in the fingers of the hand. The disease has been known since the Viking Age and is present in about 1-2% of the world's population, with a prevalence that rises to about 20% at the age of 65. This paper aims to present current knowledge related to DK. It is more common in Caucasian men, and heredity, which shows variable expression, plays a vital role in its aetiology. The etiopathogenesis of DK is still unclear and includes the formation of collagen nodules, which progress into fibrous bands between the dermis and fascia at pressure points. The diagnosis is most commonly made by clinical examination, and the treatment can be conservative or surgical. Conservative treatment is reserved for patients with mild symptoms and no finger contracture, while surgical treatment, despite frequent recurrences, is still the gold standard in therapy in situations when the contracture limits hand function and/or flexion of the metacarpophalangeal joint ≥30 degrees and/or proximal interphalangeal joint to any degree. New knowledge about the aetiology of DK would significantly contribute to more effective treatment of this relapsing progressive disease.